Ergogenic aids and the female athlete - Jordan, S. L.; Naclerio, F.; Morales, J. B. (The active female. Health issues throughout the lifespan, 2023)
Female athletes tend to choose their supplements for different reasons than their male counterparts. Collegiate female athletes report taking supplements "for their health," to make up for an inadequate diet, or to have more energy. Multivitamins, herbal substances, protein supplements, amino acids, creatine, fat burners/weight-loss products, caffeine, iron, and calcium are the most frequently used products reported by female athletes. Many female athletes are unclear on when to use a protein supplement, how to use it, and different sources of protein (animal vs. plant-based). This chapter addresses protein supplementation, amino acid supplementation, and creatine. In this chapter we also address the reported performance benefits, if any, of Echinacea, ginseng, caffeine, energy drinks, pre-workouts, and iron. The chapter concludes with a discussion on contamination of supplements and banned substances for competition. Competitive athletes should be aware of the banned substance list for their governing body and that over the counter (OTC) nutritional supplement products are not currently regulated by the food and drug administration (FDA). This lack of regulation may lead to supplements that are contaminated with banned substances.